PEMBERANTASAN TINDAK PIDANA PENYELUDUPAN BAWANG MERAH OLEH PETUGAS BEA DAN CUKAI DI WILAYAH HUKUM KOTA DUMAI - Ramadhan, Andika; ', Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The purpose of writing this thesis namely: First, Knowing the efforts made by the Customs officers in eradicating criminal onion smuggling in Dumai City Legal Areas, Second, obstacles in eradicating criminal onion smuggling by Customs officers, Third, the efforts made in overcoming obstacles in eradicating criminal onion smuggling by customs officers.The study was conducted in the unofficial ports of Dumai City, while the population and the sample were all parties concerned with the problems studied in this study, the data sources used, the primary data, the secondary data, and the tertiary data, the data collection techniques in the study this with the observation, interview and literature study.From the results of research problems there are two main things that can be concluded. First, the effort made by Customs officers in eradicating the criminal act of smuggling of onion in Dumai city law area is the participation of the society is still lacking, this is because the people feel lucky, because they can buy the goods of export of foreign origin smuggled with low price and high quality. The high cost of production makes the production less able to compete with goods produced overseas.Second, the obstacles of customs officers in eradicating Red Crime Smearing on the Dumai City Legal Territory in the form of weak coordination and cooperation between officers and inter-related agencies in the field provide opportunities for smuggling. Suggestion Writer, First, It is expected to Customs to increase patrol intensity in every territorial waters of Dumai City and its surroundings. Especially in the ports and rats (unofficial) that are not supervised by the authorities and run the provisions of customs administration consistently, considering it is very detrimental to the State of Indonesia from the tax revenue sector.Second, for the PPNS Directorate General of Customs to provide punishment and a maximum penalty for the perpetrators, in order to have a deterrent effect on the perpetrator and be a lesson for other people not to commit the criminal act of the smuggling. Third, the community is expected to participate actively in preventing the occurrence of criminal acts of smuggling, with care about the situation and conditions around each and can inform the parties to the Customs.Keywords : Customs, era dication of criminal offense, onion